Back Cover: Enhanced Ene‐Reductase Activity through Alteration of Artificial Nicotinamide Cofactor Substituents (ChemCatChem 5/2016). Issue 5 (1st March 2016) - Löw, Sebastian A.; Löw, Isabell M.; Weissenborn, Martin J.; Hauer, Bernhard
Abstract : The Cover shows a running track and three competing cofactors on their way to an enzyme. The goal is the flavin in the active side of the enzyme NADH‐dependent cyclohexenone reductase (NCR) from Zymomonas mobilis . Two of the three cofactors are artificial mimics presented in the Full Paper of S. Löw et al. Besides the electrochemical characterization of the mimics, the authors screened their activity with several enzymes and substrates. The NCR was found to be very efficient in utilizing cofactor mimics. Kinetic comparison of NADH and the mimic HPNAH with NCR and Z ‐citral as a substrate revealed a sixfold higher v max for HPNAH. This is indicated on the figure by HPNAH winning the race to the enzyme. More information can be found in the Full Paper by Löw et al. onpage 911 in Issue 5, 2016 (DOI:10.1002/cctc.201501230 ).